The Relationship between Sleep Quality and Stress Levels with The Menstrual Cycle in Final Year Midwifery Student, Faculty of Medicine, Brawijaya University - Ni Komang Yeni Patma Sari; Purwaningtyas, Nuretha Hevy; Kusumaningtyas, Dian (Journal of Issues in Midwifery, 2024)
Sari, Ni Komang Yeni Patma. 2023. The Relationship between Sleep Quality and Stress Levels with The Menstrual Cycle in Final Year Midwifery Student, Faculty of Medicine, Brawijaya University. Final Assignment. Bachelor of Midwifery Program, Faculty of Medicine, Brawijaya University. Supervisors: (1) dr. Nuretha Hevy Purwaningtyas, M.Sc., Sp. DLP (2) Dian Kusumaningtyas, S.Si.T., M.Keb Background: Stress is a condition when a person is unable to accept the demands and pressures that exist. Sleep quality can be assessed by sleep duration, sleep latency, sleep disturbance and daytime functioning. Poor sleep quality can cause physiological function disorders in the body, especially hormonal disorders related to the menstrual cycle. Every woman will experience a different menstrual cycle based on the condition of their individual bodies. Menstruation can be affected by stress levels and sleep quality. Objective: Knowing the relationship between sleep quality and stress levels with the menstrual cycle in final year midwifery students FK UB. Methods: This study used a cross sectional design. The sample used according to the inclusion and exclusion criteria was 63 students. This research instrument used PSQI questionnaire, DASS questionnaire and menstrual cycle questionnaire. Bivariate analysis was performed with Chi Square test and Fisher's Exact test, and multivariate analysis was performed with logistic regression test. Results: There was no significant relationship between sleep quality and menstrual cycle (p-value 0.584) and there was no significant relationship between stress level and menstrual cycle (p-value 0.469) in final year Midwifery students FK UB. More in-depth research is needed related to other factors that cause students' menstrual cycles to be disrupted. Keywords: Sleep Quality, Stress Level, Menstrual Cycle.